Inappropriate major histocompatibility complex class II expression by thyroid follicular cells in thyroid autoimmune disease and by pancreatic beta cells in type I diabetes. - Pujol-Borrell, R; Todd, I; Londei, M; Foulis, A; Feldmann, M; Bottazzo, G (1986)
"Inappropriate" expression of class II major histocompatibility complex (MHC) molecules by target cells has been found in all organ-specific autoimmune diseases so far examined for the presence of this phenomenon. These glycoproteins may have a functional role as class II+ thyrocytes are able to present both small fragments of foreign antigens and autoantigens to helper T cells. Interferon gamma is a likely modulator of MHC class II expression in the thyroid but other signals like thyroid-stimulating hormone seem to influence its action. By contrast, it appears that lymphokines are not involved in inducing the inappropriate MHC class II expression observed in situ in the pancreatic beta cells of diabetics. These data suggest that regulation of MHC class II expression is different in thyroid follicular cells from pancreatic beta cells, and that similar differences may be found in other cell types involved in autoimmune disease, thus reinforcing the concept of heterogeneity in the pathogenesis of organ-specific autoimmune disorders.